Improving the Eighth Grade Students’ Mastery of Verbs Using the Total Physical Response (TPR) Method - Zega, Riswan; Harefa, Wina Anjelina; Gulo, Septika Novianti; Namo, Elnardus Fransiskus Jafrinus (Universitas Pahlawan Tuanku Tambusai, 2025)
Mastering vocabulary, particularly action verbs, is fundamental for junior high school students to develop the effective communication skills in English. Although English teacher taught students with various strategies at SMP Swasta Kristen Agios Nikolaos to improve the mastery of vocabulary but almost of them still have not mastered the action verbs. This study aimed to improve the eighth graders' mastery of verbs by using the Total Physical Response (TPR) method. It was conducted in classroom action research, which included planning, action, observation, and reflection process. It was done in two cycles. The participants were 10 males and 14 females. The instruments used were observation, test, and field notes. The data were analyzed through both qualitative and quantitative approaches. The results shown that in cycle I there were 14 students (58,33%) categorized as poor, 10 Students (41,67) were categorized at good, and there were no students categorized at very good and excellent level but in cycle 2, there were no students categorized at the poor, fair, or good levels. There were 5 students (21%) categorized at very good, and 19 students (79.17%) categorized at excellent level. In addition, the classroom activities carried out by the researcher were done 94% and the students’ responses done 92%. Furthermore, the field notes showed a positive learning atmosphere. The students became more active, happy, and enjoying the learing process. In conclusion, the use of the TPR method was effective in improving the eighth graders’ verbs at SMP Swasta Kristen Agios Nikolaos.